A Study on Agricultural Sector and Sustainable Development in Maharashtra: A Critical Analysis (International Journal of Food and Nutritional Sciences, 2022)
Capital is considered to be a very important factor in the production process. Any type of business requires capitalso capital is that part of wealth that is used in the production process to increase output. A common concept ofcapital is that part of man-made wealth that is used in the production process to increase output.